Methods Of Developing Students' Spatial Imagination Using Computer Graphics In The Teaching Of Drawing - Qodirovich, Mamatov Dilshod; Jalolovich, Yadgarov Nodir; Samadovich, Azimov Sanjar; Abdurazzakovna, Rafiyeva Nargiza (The journal of contemporary issues in business and government, 2021)
According to experts, as a means of computer training, changes in the method and form of teaching are characteristic features of information technology. Therefore, the issue of identifying and generalizing the problems of teaching drawing in general secondary schools remains relevant. Because there are a number of issues related to the use of computer graphics in the process of teaching spatial geometric objects and drawing, they have been theoretically sufficiently addressed in the course of our research.